Ximenia americana L. enhances the antibiotic activity and inhibit the development of kinetoplastid parasites. (June 2019) - de Menezes, Irwin Rose Alencar; da Costa, Roger Henrique Sousa; Augusti Boligon, Aline; Rolón, Miriam; Coronel, Cathia; Vega, Celeste; Melo Coutinho, Henrique Douglas; da Costa, Maria Socorro; Tintino, Saulo Relison; Silva Pereira, Raimundo Luiz; de Albuquerque, Thais Rodrigues; da Silva Almeida, Jackson Roberto Guedes; et al.
Highlights: The main phenolic compounds identified by HPLC were quercitrine and caffeic acid. The extract demonstrated a weak anti-kinetoplstida effect. The extract enhanced the antibiotic activity of norfloxacin against S. aureus. Abstract: Objective: The objective of this work was evaluate the cytotoxic, leishmanicidal and tripanocidal activity, as well as to evaluate its antimicrobial and modulatory activity in association with different antibiotics of the hydroethanolic extract of the Ximenia Americana stem bark (EHXA). Method: In vitro tests against Trypanosoma cruzi, Leishmania sp. and citotoxicity were performed. The evaluation of the antibacterial and bacterial resistance modulatory effect was given by the microdilution method. Results: The chemical profile show different classes of compounds with significant presence of quercetrin and caffeic acid. The EHXA demonstrated activity only in the concentration of 1000 μg/mL against the L. infantum and L. brasiliensis promastigotes, causing mortality percentage of 40.66 and 27.62%, respectively. The extract presented a significant toxicity only in the concentration of 1000 μg/mL, causing a mortality of 55.42% of fibroblasts. The antibacterial activity of the EHXA demonstrated a MIC value ≥1024 μg/mL against all the tested bacteria. However, in the modulation assay with EHXA in association with different antibiotics the extract had a synergistic effect against S. aureus strains when associated with norfloxacin. Conclusion: The results of this investigation demonstrate for the first time the chemical composition of the hydroethanolic extract of the Ximenia Americana stem bark, your potential antiparasitic and modulatory effect. The low cytotoxic and biological potential against S. aureus open therapeutic perspectives against leishmaniosis and bacterial infections.